SOCIAL AND PEDAGOGICAL VIEWS OF THE JADID UZBEK THINKER ABDULLA AVLONI ON PRESERVING THE PURITY OF THE NATION'S GENE FUND (Archive of Conferences, 2021)
The article analyzes the correlation and integrative relationship of Abdullah Avloni's sociopedagogical views on the preservation of the purity of the nation's gene pool with the ecological consciousness and culture of society.